Health literacy, its importance for citizens and patients and the involvement of medical librarians: a European initiative (Journal of EAHIL, 2016)
Recent initiatives of the European Parliament highlight the importance of advancing health literacy in all memberÂ states. The project “Health literacy and health education fostering participation and improving women’s and men’sÂ health” was developed in the framework of a Grundtvig Learning Partnership – Lifelong Learning Program, funded byÂ the European Commission. Health literacy and health education empower patients and citizens to participate to the fullÂ in their health care and to communicate on eye level with their health professionals, making it possible to overcomeÂ disparities in health due to social causes. Librarians and information specialists are in a position to play a key role inÂ searching, validating and disseminating health information for the general public.